Studi Pendahuluan:Model Pembelajaran vokasional untuk Program Keahlian Tata Busana Berbasis Kearifan Lokal - Wahyu Eka Priana Sukmawaty; Sri Purwani (Universitas Sarjanawiyata Tamansiswa, 2021)
The learning process has a significant influence on graduate output and outcomes. The output of the competence of Fashion Skills to understand and apply factual, technological, artistic, cultural, and humanities knowledge with insights into humanity, nationality, statehood, and civility related to the causes of phenomena and events in a specific field of work to solve problems. While the outcome is related to the world of productive work in the field of fashion, ranging from boutiques, convection, designers, etc. To achieve maximum output and outcome, an effective learning model is needed. One such learning model is a vocational learning model based on local wisdom. To find out the detailed form of the learning model, research is carried out with the review literature method. In this research, the topic raised in the vocational learning model of the local wisdom-based fashion expertise study program. The initial stages that are carried out starting from reviewing several national and international journal articles that are relevant to the vocational learning model of the local wisdom-based fashion expertise program. After that, a review and conclusions are made of the relevant journal article.